Ants Promote Germination of the Tree Guarea guidonia by Cleaning its Seeds - Silva, Bianca Ferreira; Azevedo, Igor Henrique Freitas; Mayhé-nunes, Antonio; Breier, Tiago; Freitas, Andre Felippe Nunes De (Instituto de Florestas da Universidade Federal Rural do Rio de Janeiro, 2019)
ABSTRACT Ants interact with seeds, and frequently remove their appendages. This work aimed to evaluate the effect of ants on the germination of Guarea guidonia (Meliaceae) seeds through removing the fleshy tissue of their integument (sarcotesta). The seeds were subjected to the following treatments: control (no sarcotesta removal), manual removal, and removal by ants. The results show that germination percentage and time varied among treatments, with removal by ants showing the highest percentage within the shortest possible time. The positive effect of sarcotesta removal by ants points to a possible action of anti-fungal substances. As germination is an essential step for recruitment, ant activity may be important to the regeneration of a deforested area. Further studies should consider germination experiments under natural conditions in order to increase the understanding on plant development.
Keywords: ant-plant interaction; recruitment; seed germination; Solenopsis; Atlantic Forest